Recent Advancements in Gene Therapy for Hereditary Retinal Dystrophies - Ayşe Öner (Türk Oftalmoloji Dergisi, 2017)
Hereditary retinal dystrophies (HRDs) are degenerative diseases of the retina which have marked clinical and genetic heterogeneity. Common presentations among these disorders include night or colour blindness, tunnel vision, and subsequent progression to complete blindness. The known causative disease genes have a variety of developmental and functional roles, with mutations in more than 120 genes shown to be responsible for the phenotypes. In addition, mutations within the same gene have been shown to cause different disease phenotypes, even amongst affected individuals within the same family, highlighting further levels of complexity. The known disease genes encode proteins involved in retinal cellular structures, phototransduction, the visual cycle, and photoreceptor structure or gene regulation. Significant advancements have been made in understanding the genetic pathogenesis of ocular diseases, and gene replacement and gene silencing have been proposed as potentially efficacious therapies. Because of its favorable anatomical and immunological characteristics, the eye has been at the forefront of translational gene therapy. Recent improvements have been made in the safety and specificity of vector-based ocular gene transfer methods. Dozens of promising proofs of concept have been obtained in animal models of HRDs and some of them have been relayed to the clinic. The results from the first clinical trials for a congenital form of blindness have generated great interest and have demonstrated the safety and efficacy of intraocular administrations of viral vectors in humans. This review summarizes the clinical development of retinal gene therapy.